ANALISIS DAYA SAING MAHASISWA DALAM MEMASUKI PASAR TENAGA KERJA DI ERA INDUSTRI 4.0 (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DI KOTA PALEMBANG) - Pandriadi Pandriadi; Ikraam Ikraam (Fakultas Ekonomi Universitas IBA, 2022)
This research aims to analyze the competitiveness of students in entering labor market during industry 4.0 era. Competitiveness measured by some indicators, namely academic skill, English Skill, organization skill, entrepreneur skill and computer skill. This research is quantitative and data dissemination through questionnaire. The population in this research is students of Economic Faculty in Palembang City with the number of sample reaches 281 respondent by using purposive sampling. The data have been collected analyzed by using SPSS version 26. The results of this research show that most competitiveness of students by using all indicators are low competitiveness, except academic skill.Furthermore, this research also shows that there is competitiveness difference between students who come from state university and students who come from private university where the students from state university tend to have higher competitiveness than student from private university. Key words: Competitiveness, Students, Industry 4.0